Origin and chronology of sandy substrates supporting open vegetation ecosystems in Amazonia - Rodrigues, Fernanda Costa Gonçalves (2022)
The Amazonia biome hosts upland closed and open vegetation ecosystems, in which the current biogeographical patterns are intricately linked to changes of the physical landscape. Open vegetation ecosystems, especially white-sand ecosystems (WSE) and savannas, have long been thought as key environments of biotic diversification in Amazonia. Understanding the origin, resilience and dynamics of the substrates supporting different ecosystems is indispensable for better comprehension of Amazonian biogeography. Here we investigate the spatial distribution of Amazonian open vegetation ecosystems and their physical landscape, represented relief and type and age of geological substrates. To achieve this aim, we selected sandy substrates areas in central and eastern Amazonia, which were characterized through the application of (i) optically stimulated luminescence (OSL) and thermally transferred (TT) OSL dating, (ii) OSL and thermoluminescence (TL) sensitivity analyses as sedimentary history tracer, (iii) textural and compositional analyses (i.e., grain size, X-ray fluorescence (XRF) and magnetic susceptibility), combined with (iv) a comprehensive review on the substrate origins of different open vegetation ecosystems across Amazonia. Open vegetation ecosystems in Amazonia can be divided as occurring in highland or lowland areas. In the highlands, long-term exhumation and weathering of pre-Cenozoic rocks render more stable upland areas over time. Whereas in lowland Amazonia, the rapidly changing landscape due to the fluvial and eolian systems dynamics can expand or retract sandy substrates and their overlying open vegetation more frequently. The widespread occurrence of savannas and WSE upon the extensive sandy alluvial plains in Negro and Branco Rivers basins are associated to high permeability and repeated rising and falling of the water table, favoring the development of spodosols in that area. These sandy substrates present luminescence ages ranging from almost 2 Ma to 0.9 ka. These ages are discussed in terms of potential geomorphic processes leading to the formation of substrates (solar resetting by soil mixing processes and surface transport or apparent age of the parent bedrock). TT-OSL ages ranging from 2 Ma to 23 ka were primarily interpreted as depositional ages of fluvial sediments, which formed upland terraces after channel incision. OSL ages ranging from 68 ka to 0.9 ka can be interpreted as sedimentation ages or solar resetting by soil processes. OSL equivalent dose distributions with high overdispersion, and overall constancy in grain size statistics, BOSL and TL sensitivities and Zr/Ti and Zr content suggest homogenization of sandy substrates via soil mixing processes. In this case, luminescence ages would represent minimum dates for sandy substrate development. However, the possibility of such ages representing the time of sand deposition cannot be ruled out. The coupling between OSL and TT-OSL dating techniques allow us to date sedimentary deposits covering the whole Quaternary, which implies a new time window for the Amazonia history. The availability of sandy substrates supporting open vegetation ecosystems change in multiple spatiotemporal scales, and depends on local conditions, such as water table depth, surface elevation and primary sediment grain size, which can lead to decoupling between regional climate patterns and spatial distribution of open vegetation ecosystems. Thus, the development of sandy substrates would rely on local geological controls, favoring open vegetation ecosystems with fragmented spatial distribution and varied temporal persistence.